The Study Examines the Marketing Strategies of Goat and Sheep Farming Businesses in CV. Fajar Randu - K A Usman; F Hasan; S Mulatsih (Talenta Publisher, 2024)
The livestock sector has a very broad and systematic scope. Within the livestock business, the marketing function plays a crucial role. Marketing is based on the basic marketing code and is designed to emulate or function as part of a marketing system. Goat and sheep farming businesses are in great demand, both for daily needs and for religious celebrations. CV Fajar Randu's goat and sheep farming business is a farm that provides goat and sheep buying and selling, aqiqah, and qurban services.The types of goats and sheep raised here are local kacang goats and sheep, with varying prices offered. This research aims to identify the marketing and financial channels of CV Fajar Randu. The research was carried out in August-April 2023. The methods used in collecting data were interviews, observation, and questionnaires, while determining the research sample used a purposive sampling technique. The research results show that there are two marketing channels that occur, namely level I channels and level II channels and the marketing functions carried out by CV Fajar Randu are the exchange function and the physical supply function. Level I marketing channels have the smallest marketing margin, the largest farmer's share, and the most efficient marketing channel. The SWOT analysis results indicate that CV Fajar Randu is in quadrant I. The research results also show that the environmental conditions of CV Fajar Randu are good. According to the research findings, the CV Fajar Randu farm can employ SO as an alternative strategy. In conclusion Level I marketing channels is the most efficient ones